Q.P. North, Trinidad - (:unkn) unknown (My University, 2009)
A picture of a carriage on the road alongside the Queen's Park Savannah. Everywhere a variety of tropical trees.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Savannas--Trinidad and Tobago; Trees--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Roads--Trinidad and Tobago; Fences--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Transportation--Trinidad and Tobago; [1907]; Queen's Park Savannah (Port of Spain)